Indigenous Fruit Trees in the Tropics: Domestication, Utilization and Commercialization 2007
DOI: 10.1079/9781845931100.0224
|View full text |Cite
|
Sign up to set email alerts
|

Marketing of indigenous fruits in Southern Africa.

Abstract: During the 1999-2000 indigenous fruit ripening season, a detailed marketing research study was conducted in Zimbabwe to generate baseline information on the prevailing marketing system for Uapaca kirkiana and Strychnos cocculoides, including consumer preferences and willingness to pay for the fruits. The study also explored the possibility of expanding marketing opportunities for these fruits. This chapter discusses the interesting findings of this study. It describes the marketing chain, characterization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In Zimbabwe, for example, wild fruit trees represent about 20% of total woodland resource use by rural households (Campbell et al 1997) and fruits of Uapaca kirkiana (Muell., Arg), Ziziphus mauritiana (Lam), Strychnos cocculoides (DC ex Perleb) and Parinari curatellifolia (Planchon ex Benth.) are sold to buy staple food and other household goods (Ramadhani, 2002;Mithofer, 2004). Producers can obtain substantial household incomes supplying local markets (Kaaria 1998, Schomburg et al 2002, Ramadhani 2002, with women and children being the main beneficiaries, although men dominate transport business and the wholesale market.…”
Section: Towards the Development Of Miombo Fruit Trees As Commercial mentioning
confidence: 99%
See 1 more Smart Citation
“…In Zimbabwe, for example, wild fruit trees represent about 20% of total woodland resource use by rural households (Campbell et al 1997) and fruits of Uapaca kirkiana (Muell., Arg), Ziziphus mauritiana (Lam), Strychnos cocculoides (DC ex Perleb) and Parinari curatellifolia (Planchon ex Benth.) are sold to buy staple food and other household goods (Ramadhani, 2002;Mithofer, 2004). Producers can obtain substantial household incomes supplying local markets (Kaaria 1998, Schomburg et al 2002, Ramadhani 2002, with women and children being the main beneficiaries, although men dominate transport business and the wholesale market.…”
Section: Towards the Development Of Miombo Fruit Trees As Commercial mentioning
confidence: 99%
“…are sold to buy staple food and other household goods (Ramadhani, 2002;Mithofer, 2004). Producers can obtain substantial household incomes supplying local markets (Kaaria 1998, Schomburg et al 2002, Ramadhani 2002, with women and children being the main beneficiaries, although men dominate transport business and the wholesale market. In the Zambezi valley, 80% of indigenous fruit producers/collectors process fruits for home consumption (Kadzere et al 2001), while in South Africa 94% of households use S. birrea fruits for making beer, jam and juice (Shackleton 2004 ), but little consideration is given to hygiene (Mumba et al 2002).…”
Section: Towards the Development Of Miombo Fruit Trees As Commercial mentioning
confidence: 99%
“…However, there seems to be no relationship between taste and size of the fruit which complicates the choice of selection criteria. Ramadhani and Schmidt (2008) reported that consumer preference and willingness to buy fruits is not always dictated by fruit size but taste as well. For instance, small tasty fruits were considered good quality fruit which may apply to baobabs fruits as well.…”
Section: Fruit Variation Between and Within Provenancesmentioning
confidence: 99%
“…The results have shown that fruit weight can be emphasized in the course of trade where people prefer bigger fruits. However, further research needs to be conducted in order to determine whether the bigger fruits are also sweet because consumers preferences may be based not only on fruit size but also on taste [24,25]. The variation is of significance if the fruit weight is to be improved; then provenances that can be used in vegetative propagation can be easily chosen.…”
Section: Variation In Fruit Characteristics Among Provenancesmentioning
confidence: 99%